2015
DOI: 10.1039/c5cc05548b
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to fabricate composite thin films with tunable micro- and nanostructures via self-assembly of block copolymers

Abstract: A new and facile strategy to fabricate composite thin films with tunable morphologies via self-assembly of block copolymer molecules at the air/liquid interface is first reported. The morphologies (parallel nanowires and foams) of these freestanding thin films can be tuned by varying the molecular structure or other experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Figure a shows that there are indeed Au–N interactions by the presence of the Au–N Raman band (232 cm –1 ) in the SERS spectra of the nanosensors with no or short time exposure to Hg 2+ (Figure a), in addition to Au–S binding. This is consistent with various reports that found that the pyridyl nitrogen atom can easily interact with metal ions and that this coordination mainly occurs via σ-electron donation from N to metal ions with negligible π back-bonding from the metal ion. ,,, With increasing Hg 2+ incubation time, a Raman peak for Hg–N (220 cm –1 ) appears in the SERS spectra (Figure a). In addition, a shift of the out-of-plane C–H deformation band at around 708 cm –1 to lower frequencies (Figure b) is similar to what is observed in other pyridine complexes with transition metals. , Furthermore, the intensity ratio, I 1573 / I 1604 , of the Raman peaks at 1573 (asymmetric stretching) and 1604 cm –1 (symmetric stretching), associated with the ring stretching of pyridyl, decreases with incubation time until reaching a plateau at 30 min (Figure a), which is consistent with the trend in I 708 / I 428 with incubation time.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Figure a shows that there are indeed Au–N interactions by the presence of the Au–N Raman band (232 cm –1 ) in the SERS spectra of the nanosensors with no or short time exposure to Hg 2+ (Figure a), in addition to Au–S binding. This is consistent with various reports that found that the pyridyl nitrogen atom can easily interact with metal ions and that this coordination mainly occurs via σ-electron donation from N to metal ions with negligible π back-bonding from the metal ion. ,,, With increasing Hg 2+ incubation time, a Raman peak for Hg–N (220 cm –1 ) appears in the SERS spectra (Figure a). In addition, a shift of the out-of-plane C–H deformation band at around 708 cm –1 to lower frequencies (Figure b) is similar to what is observed in other pyridine complexes with transition metals. , Furthermore, the intensity ratio, I 1573 / I 1604 , of the Raman peaks at 1573 (asymmetric stretching) and 1604 cm –1 (symmetric stretching), associated with the ring stretching of pyridyl, decreases with incubation time until reaching a plateau at 30 min (Figure a), which is consistent with the trend in I 708 / I 428 with incubation time.…”
Section: Resultssupporting
confidence: 91%
“…With this in mind, we herein report on SERS-active nanofibers decorated with 4-mercaptopyridine (4-Mpy)-modified AuNPs for the sensitive and selective detection of Hg 2+ and Ag + (Scheme A). 4-Mpy can adsorb onto the Au surface through its thiol group, N atoms, or π electrons and can interact with Hg 2+ and Ag + through its pyridyl group. , We will show that upon coordination with metal ions, the orientation of the 4-Mpy molecules adsorbed on AuNPs changes from nominally flat to perpendicular (Scheme B), modifying the intensity ratio of the SERS signal and enabling the quantitative determination of Hg and Ag ions in aqueous solution. This addresses an important challenge, considering that fluorescent probes for the detection of metal ions in cells require cell membrane permeability or even functionalization for specific targets located at different subcellular structures. In contrast, our nanosensors enable detection at the single-cell level due to their advantages for intracellular studies, thanks to their sub-micron size that minimizes cell damage and provides high spatial resolution and improved SERS sensitivity related to a lens effect. As a proof of concept, we will demonstrate the use of SERS-active nanofibers decorated with 4-Mpy-modified AuNPs for the detection of Hg ions in the nucleus and cytoplasm of living breast cancer cells (MCF-7).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…1,2 Biolike membrane structures have been mimicked via self-assembly of amphiphilic block copolymers, albeit typically with much larger molecular weight polymers relative to lipids. 3,4 Amphiphilic block copolymers are composed of a hydrophobic domain and a hydrophilic domain and are known to self-assemble thermodynamically into spherical micelles, worm-like micelles, bilayers, and other structures, depending on the ratio of hydrophobicity to hydrophilicity. 57 Furthermore, they have shown increased morphological flexibility when compared with lipids, as well as the ability to possess additional functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, a wide range of structural architectures and functional responses are formed through lipid assemblies, leading to essential roles in a number of physiological processes. , Biolike membrane structures have been mimicked via self-assembly of amphiphilic block copolymers, albeit typically with much larger molecular weight polymers relative to lipids. , Amphiphilic block copolymers are composed of a hydrophobic domain and a hydrophilic domain and are known to self-assemble thermodynamically into spherical micelles, worm-like micelles, bilayers, and other structures, depending on the ratio of hydrophobicity to hydrophilicity. Furthermore, they have shown increased morphological flexibility when compared with lipids, as well as the ability to possess additional functionality. ,, Such functionality can be introduced through the incorporation of nanoparticles (NPs), organic molecules, and functional groups. For example, magnetite (Fe 3 O 4 ) nanoparticles were encapsulated by modified poly­(ethylene oxide)–poly­(propylene oxide)–poly­(ethylene oxide) (PEO–PPO–PEO) triblock copolymer and used effectively as a temperature-responsive material for targeted drug delivery. , Mai and Eisenberg incorporated magnetic nanoparticles into the central compartment of a number of different copolymer architectures, including vesicles, rods, and micelles. , Likewise, Hickey et al.…”
Section: Introductionmentioning
confidence: 99%